(untitled) (Interdisciplinary Studies Journal, 2024)
Based on the discussion that took place between drag artists RuPaul Charles and Pabllo Vittar on the social network Twitter, this article aims to analyze the use of old age as a form of oppression. The netnographic study consists of a sample composed of 70 tweets collected in 2022. The results indicate the scarcity of studies around the phenomenon of old age related to the craft of drag art. Six categories of analysis were constituted, stating that old people: must be mature, are old, are envious, are bitter, have reduced mental capacity, are repressed. Old age is used as a form of oppression and defines an aesthetic/productive disability at the moment when it is socially decided that everything old becomes useless. The findings indicate the need for a change in the attitude of the field of aging studies, which, for the most part, considers it as a universal stage.